SOSIALISASI BAHAYA PERGAULAN BEBAS DI ERA GENERASI Z PADA USIA 17-20 TAHUN DI RT 03/RW04 MARGAJAYA - BEKASI SELATAN, KOTA BEKASI - Indriani Rahayu NingTyas; Dian Wahyudin; Faizah Julina; Renisya Ayu Utami; Ambarwati Ambarwati (Batara Wisnu : Indonesian Journal of Community Services, 2023)
Promiscuity can have a negative impact on the psychological and emotional well-being of individuals, increase the risk of spreading sexually transmitted diseases, and damage moral values ??in society. These findings highlight the need for an active role for families, education and society in forming awareness of the dangers of promiscuity and encouraging more socially responsible and healthy behavior. This Community Service aims to educate about the dangers of promiscuity for teenagers in the surrounding environment. Socialization of the Dangers of Promiscuity at the age of 17 to 20 years, especially in the context of Generation Z who live in the era of digital and globalization. Socialization regarding the dangers of this free behavior is considered important to understand teenagers about the negative consequences that may arise from their life choices. The research method involved surveys and interviews to collect data from a Generation Z sample spanning a defined age group. Data analysis was carried out to identify behavioral patterns, driving factors, and the social and psychological impacts of promiscuity among teenagers. It is hoped that the findings of this research will provide a deeper insight into the urgency of socializing the dangers of promiscuity and designing more effective strategies to prevent and overcome this phenomenon in the context of Generation Z.